The Turkish geopolitical role in the Syrian crisis: A study in political geography. - Najem, Rafal Hussein; Kadhim, Raid Ataallah (International Journal of Psychosocial Rehabilitation, 2020)
The present study tackles the geopolitical characteristics of the state of Turkey. The ability of Turkey to benefit from the natural and human characteristics in favor of its strategy towards the countries of the region in order to have an effective role at all levels is a topic that is given a great deal of discussion in the present study. The Syrian crisis reveals many aspects of the Turkish strategy in the region.